Nuclear localization of EIF4G3 suggests a role for the XY body in translational regulation during spermatogenesis in mice†. Issue 1 (17th November 2017) - Hu, Jianjun; Sun, Fengyun; Handel, Mary Ann
ABSTRACT: Eukaryotic translation initiation factor 4G (EIF4G) is an important scaffold protein in the translation initiation complex. In mice, mutation of the Eif4g3 gene causes male infertility, with arrest of meiosis at the end of meiotic prophase. This study documents features of the developmental expression and subcellular localization of EIF4G3 that might contribute to its highly specific role in meiosis and spermatogenesis. Quite unexpectedly, EIF4G3 is located in the nucleus of spermatocytes, where it is highly enriched in the XY body, the chromatin domain formed by the transcriptionally inactive sex chromosomes. Moreover, many other, but not all, translation-related proteins are also localized in the XY body. These unanticipated observations implicate roles for the XY body in controlling mRNA metabolism and/or "poising" protein translation complexes before the meiotic division phase in spermatocytes. Summary Sentence: In spermatocytes, translation initiation factor EIF4G3 localizes almost exclusively to the XY body, suggesting a role for this chromatin domain in post-transcriptional regulation of spermatogenic gene expression.